Imposing calculations: The visibility and invisibility of harm in the Mackenzie Gas Project environmental assessment - Dokis, Carly (Frontiers in Sociology, 2023)
Environmental assessment is an institutional apparatus through which proponents concede harm associated with extractive projects. Within these processes’ proponents define the nature and scope of harm, which is made visible through the production of indicators and measurements and made manageable through mitigation measures or economic compensation. That the activities of extractive industries may have effects on surrounding ecologies is rarely in question; proponents of extractive projects regularly concede that their activities will result in negative (but also positive) changes to environments and communities. What is often contested in the course of environmental assessment and regulatory processes is the “significance” of the impacts identified; the nature of the harm caused, and whether or not it is possible or acceptable to accommodate it. Drawing from ethnographic fieldwork conducted in the Sahtu Settlement Area, NWT during the Mackenzie Gas Project environmental assessment, along with regulatory documents and transcripts, this paper examines how proponents and regulatory regimes work to make the impacts of extractive industries visible, and how these logics deviate discursively and materially from many Indigenous peoples’ understandings of appropriate relationships between human beings and nature.